COVID-19’s Impact on Food Security among Urban Refugee Youth in Kenya: A Postcolonial Feminist Perspective (African Human Mobility Review, 2025)
This study analyzes the experiences of urban refugee communities, more specifically, thechallenges young South Sudanese refugees living in Kenya face. We divert from thecomprehensive examination of refugees in camps to focus on urban youth amid Kenya’s refugeepolicy changes and the impact of the COVID-19 pandemic. With the support of South Sudanesecommunity leaders, our study engaged 58 participants – 42 males and 16 females. Participantsengaged in semi-structured discussions about food security and other daily challenges related totheir urban refugee experience. This study draws on postcolonial feminist theory to contextualizethe gender-specific dimensions of food insecurity, centering analysis on discussing historicalpower structures, migration patterns, urbanism theory, and geopolitical influences contributing tothe experiences of South Sudanese urban refugee youth in Kenya. Study participants, irrespectiveof location, encountered corruption, limiting policies, and conflicting identity formation, withwomen specifically highlighting self-identity, dignity, and family as critical to supporting theirresilience. Participants emphasized the impact of COVID-19 on community cohesion, particularlyin shared meals. However, their agency was hindered by movement restrictions, invisible fences,or barriers exacerbated by unequal support and aid distribution. The research advocates for theformulation of clear African contextualized urban-based policies and migration systems thatprioritize the needs of urban refugees, safeguarding their rights and upholding human dignity.Collaborative engagement with all stakeholders within local communities, especially youthrefugees, is necessary to develop effective urban policies that promote stability, economicadvancement, and social integration.